Analisis Logam Berat Timbal Pada Kangkung Air Di Sungai Manembo-Nembo Menggunakan Spektrofotometri Serapan Atom - Rasubala, Yitro C; Tani, Djefri; Saiya, Abdon (General Chemistry Journal, 2023)
The river becomes a final disposal place for waste and causes pollution, one of which is the heavy metal lead (Pb) pollution. Water spinach cultivated in rivers can be a medium for spreading Pb because they have the ability to absorb that. This study aims to determine the levels of Pb contained in water spinach plants grown in the Manembo-nembo river and to determine the level of consumption of water spinach grown in the area. In this study, analysis was carried out using Atomic Absorption Spectrophotometry (AAS). The results of the analysis of Pb levels using AAS in the first treatment, namely the sample washed with the physiological position of leaf shoots:8.03 mg/kg, third leaf:20.1 mg/kg, fifth leaf:20.22 mg/kg, and for second treatment , the samples were not washed with the shoot physiological position: 20.03 mg/kg, the third leaf: 21.67 mg/kg, the fifth leaf position: 21.04 mg/kg. The high levels of Pb in all samples have passed the maximum threshold for lead metal content in food, especially fruit and vegetables according to the Indonesian National Standard (SNI) 2009, which is 0.5 mg/kg. This means that the water spinach plants in the Manembonembo river basin are not suitable for consumption.